Distortion of Indonesian Politics in the 2024 General Election: Case Study of Constitutional Court Decision No.90/PUU-XXI/2023 - Kopong, Elias Daton; Widodo, Pujo; Syahtaria, Ikhwan; Sukendro, Achmed (CV. Rayyan Dwi Bharata, 2025)
General elections are one of the instruments in the political systems of democratic countries in the world. In its implementation, it always uses an agreed system in the form of statutory regulations. The formulation of the regulations used is based on the political system, culture and social characteristics of each country. However, in reality, conflicts often arise which result in the quality of democracy decreasing. The things that underlie the emergence of conflict are differences in interests, goals and ideologies. The problems in the general election described above also occurred in the 2024 Indonesian general election, where the constitution was changed to suit the political interests of certain groups. This is categorized as political distortion. Changes in the conditions of the president and vice president cause political distortions in the 2024 Indonesian general election. The result is how the powers that be undermine the constitution to make nominating the vice president easier. The president and vice president must be at least forty years old. The Constitutional Court's changes added a new clause that covers people who have served as regional heads. The public responded to this as an attempt by the Constitutional Court, led by Anwar Usman, uncle of Gibran Rakabuming Raka, to pass President Joko Widodo's son.